Eugenika dalam Pandangan Agama Sebuah Tantangan Etis dalam Islam: Sebuah Tantangan Etis dalam Islam - Abdullah Hamdani Husain; Bahrevy Ahmad; Muhammad Aniq Hasan Albana; Muhamad Syauqi Mubarok (Pustaka Peradaban, 2024)
This article aims to delve into the human genome, which opened profound insights into genetic codification, sparking debates between scientific knowledge and religious beliefs, particularly in Islam. The article explores the Islamic perspectives on Eugenics, especially in the face of evolving eugenics concepts and related ethical issues. The complex context created by the history of Eugenics from ancient Greece to its tragic implementation by the Nazi regime in Germany is examined. The Islamic viewpoint, focusing on the prohibition of killing children and the ethical intricacies of abortion, is emphasized. The Quran asserts that the fear of poverty is not a valid reason to end a life. The research methodology employed in this article is a literature review approach, utilizing comparisons, differences, and potential convergence points in their thoughts. Research findings indicate differences in scholars' views on the ethics and controversies surrounding Eugenics in the context of genetic engineering. There are discrepancies in granting permissibility depending on the fetus's age, creating a complex foundation for discussions within the Islamic legal framework. Islamic perspectives on Eugenics reflect a diversity of scholars' interpretations, with many declaring its prohibition, aligning Sharia principles with the uncertainty of genetic impacts. While some permit it, such views still require deep ethical considerations. The article aims to describe the complexity of integrating genetic knowledge and religious values in addressing contemporary genetic challenges. Artikel ini bertujuan untuk mendalami penemuan genom manusia yang membuka wawasan mendalam terhadap kodifikasi genetik, memicu perdebatan antara pengetahuan ilmiah dan keyakinan agama, khususnya dalam Islam. Dalam artikel ini dieksplorasi pandangan Islam terhadap Eugenika, terutama dalam menghadapi perkembangan konsep eugenika dan isu-isu etis yang terkait. Sejarah Eugenika dari Yunani kuno hingga implementasi tragis oleh rezim Nazi Jerman menciptakan konteks yang kompleks. Pandangan agama Islam, berfokus pada larangan membunuh anak-anak dan kompleksitas etika pengguguran janin. Al-Quran menegaskan bahwa ketakutan akan kemiskinan bukan alasan sah untuk mengakhiri kehidupan. Metode penelitian yang digunakan dalam artikel ini adalah pendekatan penelitian kepustakaan dengan memanfaatkan perbandingan, perbedaan, dan titik korvengensi potensial dalam pemikiran merka. Temuan penelitian menunjukkan bahwa ada perbedaan pandangan ulama terkait etika dan kontroversi seputar Eugenika dalam rangka rekayasa genetika. Terdapat perbedaan dalam memberikan kebolehan tergantung usia janin, menciptakan landasan diskusi yang kompleks dalam kerangka hukum Islam. Pandangan Islam terhadap Eugenika mencerminkan keragaman interpretasi ulama. Sebagian besar menyatakan keharaman, mencocokkan prinsip syariah dengan ketidakpastian dampak genetik. Sementara ada yang memberikan kebolehan, pandangan ini masih memerlukan pertimbangan etis yang mendalam. Penulisan artikel bertujuan untuk menggambarkan kompleksitas integrasi pengetahuan genetika dan nilai-nilai agama dalam menghadapi tantangan genetika kontemporer.